Elevated pCO2 alters the interaction patterns and functional potentials of rearing seawater microbiota. (15th October 2021) - Lin, Weichuan; Lu, Jiaqi; Yao, Huaiying; Lu, Zhibin; He, Yimin; Mu, Changkao; Wang, Chunlin; Shi, Ce; Ye, Yangfang
Abstract: Mean oceanic CO2 values have already risen and are expected to rise further on a global scale. Elevated p CO2 (eCO2 ) changes the bacterial community in seawater. However, the ecological association of seawater microbiota and related geochemical functions are largely unknown. We provide the first evidence that eCO2 alters the interaction patterns and functional potentials of microbiota in rearing seawater of the swimming crab, Portunus trituberculatus . Network analysis showed that eCO2 induced a simpler and more modular bacterial network in rearing seawater, with increased negative associations and distinct keystone taxa. Using the quantitative microbial element cycling method, nitrogen (N) and phosphorus (P) cycling genes exhibited the highest increase after one week of eCO2 stress and were significantly associated with keystone taxa. However, the functional potential of seawater bacteria was decoupled from their taxonomic composition and strongly coupled with eCO2 levels. The changed functional potential of seawater bacteria contributed to seawater N and P chemistry, which was highlighted by markedly decreased NH3, NH4 + -N, and PO4 3- -P levels and increased NO2 − -N and NO3 − -N levels. This study suggests that eCO2 alters the interaction patterns and functional potentials of seawater microbiota, which lead to the changes of seawater chemical parameters. Our findings provide new insights into the mechanisms underlying the effects of eCO2 on marine animals from the microbial ecological perspective. Graphical abstract: Image 1 Highlights: More simplified and modularized bacterial networks of rearing seawater under elevated p CO2 . Changed abundances of CNPS cycling genes of seawater microbiome under elevated p CO2 . Changed C, N, and P chemistry of rearing seawater under elevated p CO2 . Seawater C, N, and P chemistry may be affected by future elevated p CO2 via seawater microbiome.